Organizational commitment of secondary school teachers - Gökyer, Necmi (Sakarya University, 2017)
This study aims to determine the organizational commitment of secondary school teachers to their schools, colleagues, the teaching profession and instructional work. The population of this descriptive survey consisted of 1,602 teachers who were working at 55 secondary schools located in Elazig city center during the 2016-2017 school year. The data collection tool was distributed to 460 teachers working at 11 randomly selected schools. However, data from 349 teachers were analyzed. The data collection tool consisted of two sections. The first section included conceptual questions, and the second section included items about teachers’ organizational commitment behaviors. The results showed that teachers were “always” committed to an advanced sense of duty, and “often” committed to colleagues, the teaching profession, school development and the entire scale. Male teachers were more committed to the teaching profession. They stated more than their female counterparts that they would choose the profession even if they did not have to work, that they were proud of the profession, they saw it as an ideal profession, that they wanted to have recognition, and that they viewed choosing the profession as the most positive decision in their lives. © The Turkish Online Journal of Educational Technology.
Keywords: Commitment to the teaching profession; Organizational commitment; Secondary school